Investigation of electromagnetic shielding properties of boron, carbon and boron-carbon fibre hybrid woven fabrics and their polymer composites - SANCAK, ERHAN; MISTIK, SÜLEYMAN İLKER (TAYLOR & FRANCIS LTD, 2017)
The growth of the electronic industry and the widespread use of electronic equipment in communications, computations, automations, biomedicine, space and other purposes have led to many electromagnetic interference (EMI) problems as systems operate in close proximity. It is likely to become more severe in the future, unless proper EMI control methodology and techniques are used to meet the electromagnetic compatibility requirements. In recent years, electromagnetic (EM) waves in the 1-10 GHz range are broadly used in wireless communication tools and local area networks. In the future, the usable range of EM waves will tend to shift further to higher frequency regions with the development of information technology as well as electronic devices. As a consequence, the seriousness of problems such as EMI of electronic devices and health issues is ever rising. In this study, electromagnetic shielding effectiveness, absorbance and reflectance properties of the boron, carbon and boron-carbon plain woven fabrics and boron/polyester, carbon/polyester, and boron-carbon/polyester hybrid composites were investigated. Using a coaxial transmission line holder set-up, the (EMSE), reflectance and absorbance of various fabrics and composites were carried out in the frequency range from 15 to 3000 MHz.
Keywords: Boron fibre; carbon fibre; electromagnetic shielding effectiveness (EMSE); composite; SINGLE JERSEY FABRICS; KNITTED FABRICS; STAINLESS-STEEL; YARNS; WIRE